LEMMA HENSTOCK PADA INTEGRAL M_α - Muslich Muslich (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2012)
Based on the McShane partition and McShane integral, it can be arranged the partition and integral concepts. Furthermore, it is discussed some simple properties of integral and Lemma Henstock.